Social Media Followers Influence Banking Stock Prices in Indonesia - Kartawinata, Budi Rustandi; Akbar, Aldi; Wardhana, Aditya; Maharani, Dyah (Journal of Social Science Utilizing Technology, 2023)
Background. Progress in a country can be seen from the development of the capital market, because the capital market plays a very important role in transforming and advancing a country's economy so that it grows and develops. Indonesia is a country known to be rich in natural resources, so the development of capital markets in Indonesia is a step towards sustainable economic development. Purpose. The purpose of this study is to determine the effect of social media on the economic, social and political sectors. Method. The research used is quantitative research with descriptive and verification research methods. Results. The result of this study is that the influence of the number of social media followers on the share price of banks in Indonesia shows a positive correlation between the two. In this context, banks need to utilise social media more effectively as a marketing tool, pay attention to reputation risk management, improve transparency and communication with investors, and strengthen the role of regulators in monitoring the impact of social media.. Conclusion. With this research, there is a finding that in the field of social media, there are variables that influence the financial sector, in this case, company finances, namely the number of followers of a social media platform will influence stock prices. This should be a concern for stakeholders in the business sector to pay attention to social media developments occurring in Indonesia